PENINGKATAN KEMATANGAN KARIER MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DAN PENGGUNAAN BOARD GAME CAREER RACING PADA PESERTA DIDIK KELAS XII: Penerapan Model Problem Based Learning dan Penggunaan Board Game Career Racing Dalam Peningkatan Kematangan Karier Peserta Didik - Kristin, Firosalia; Tritjahjo Danny Soesilo; Yustinus Windrawanto; Aurellia Jeslyn; Adi Nurhidayat (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
Many high school students lack certainty in determining their future careers after graduation. This quasi-experimental study examined the significant improvement in career maturity of grade 12 students through the application of Problem-Based Learning (PBL) and the use of a career guidance board game, "Career Racing," in group guidance. The subjects were 10 students from grade 12 IPS 1 selected using purposive random sampling based on low and moderate career maturity characteristics. Data were collected through observation and a career maturity scale developed based on Donald Super's theory of career maturity. Data analysis employed the Mann-Whitney U test to compare the career maturity levels of the experimental and control groups after treatment. The results showed a significant difference in post-test career maturity scores between the experimental and control groups (asymp. sig. = 0.046), with the experimental group exhibiting a higher mean rank (6.83) than the control group (3.50). Therefore, the career maturity of the grade 12 students improved significantly through the implementation of PBL and the use of the "Career Racing" board game.